The tardocolonial Latin America University: The case of Santafé in la Nueva Granada. 1800-1810 - Uribe Ángel, Jorge Tomás (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
At the end of the colonial period it was clear that the creole initiatives in the higher education replaced the metropolis ones. These initiatives preceded those of the illustrated group in other fields as the economy and especially in politics. These changes took place before the Declaration of Independence. These changes showed that neogranadinos teachers did not continue a program determined for the learning of enlighten contents into the classrooms. Then, these teachers had roles during the independence. At the same time, the Spanish authorities were provided with the criterion of the Creoles for the adoption of study plans, especially, in relation with the centers of education of the towns.